2021
DOI: 10.1186/s12883-021-02241-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term anti-seizure medication monotherapy on all-cause death in patients with post-stroke epilepsy: a nationwide population-based study in Taiwan

Abstract: Objective We aim to compare the effect of long-term anti-seizure medication (ASM) monotherapy on the risk of death and new ischemic stroke in patients with post-stroke epilepsy (PSE). Patients and methods We identified all hospitalized patients (≥ 20 years) with a primary diagnosis of ischemic or hemorrhagic stroke from 2001 to 2012 using the National Health Insurance Research Database in Taiwan. The PSE cohort were defined as the stroke patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…A long-term population-based study in the United States reported a mean mRS score of 3.3 in 35 patients after early or late seizures following an ischemic stroke, 9 which was comparable with this study. The relatively low proportion of female cases (38.4%) was similar to those in a nationwide populationbased study in Taiwan (37.4%) 25 and a single-center retrospective study in Italy (34.6%). 26 This was probably due to the higher risk of stroke 27,28 and PSE 3,28 in males.…”
Section: Discussionsupporting
confidence: 81%
“…A long-term population-based study in the United States reported a mean mRS score of 3.3 in 35 patients after early or late seizures following an ischemic stroke, 9 which was comparable with this study. The relatively low proportion of female cases (38.4%) was similar to those in a nationwide populationbased study in Taiwan (37.4%) 25 and a single-center retrospective study in Italy (34.6%). 26 This was probably due to the higher risk of stroke 27,28 and PSE 3,28 in males.…”
Section: Discussionsupporting
confidence: 81%
“…LEV and LTG had superior tolerability compared to CBZ, but no differences in seizure freedom were noted. It should be noted that these results come from studies with relatively small sample sizes [50][51][52].…”
Section: Blood-brain Barrier Dysfunction Increases Thetamentioning
confidence: 87%
“…This confirms that the newer drugs have much more tolerable adverse and fewer side effects. Additionally, focal epileptic patients were better able to tolerate 2nd generation drugs LEV and LTG when compared to the 1st generation drug CBZ [50][51][52].…”
Section: Blood-brain Barrier Dysfunction Increases Thetamentioning
confidence: 99%
“…16 Choice of ASM monotherapy in the post-stroke epilepsy setting has also been shown to affect the relative risks of subsequent cardiovascular and all-cause death. 17,18 Since epilepsy is a chronic condition, often requiring life-long ASM treatment, the impact of an ASM on CCV risk factors is an important consideration when choosing treatment in order to reduce the risk of stroke and myocardial infarction over the long term. 10 As a potent enzyme inducer, carbamazepine (CBZ) can lead to changes in lipid parameters via effects on enzymes involved in endogenous metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%